Affective, Social, and Informative Gestures Reproduction in Human Interaction: Hyperscanning and Brain Connectivity. Issue 3 (4th May 2021) - Balconi, Michela; Fronda, Giulia; Bartolo, Angela
Abstract: Gestural communication characterizes daily individuals' interactions in order to share information and to modify others' behavior. Social neuroscience has investigated the neural bases which support recognizing of different gestures. The present research, through the use of the hyperscanning approach, that allows the simultaneously recording of the activity of two or more individuals involved in a joint action, aims to investigate the neural bases of gestural communication. Moreover, by using hyperscanning paradigm we explore the inter-brain connectivity between two inter-agents, the one who performed the gesture (encoder) and the one who received it (decoder), with functional Near-infrared Spectroscopy (fNIRS) during the reproduction of affective, social and informative gestures with positive and negative valence. Result showed an increase in oxygenated hemoglobin concentration (O2Hb) and inter-brain connectivity in the dorsolateral prefrontal cortex (DLPFC) for affective gestures, in the superior frontal gyrus (SFG) for social gestures and the frontal eye fields (FEF) for informative gestures, for both encoder and decoder. Furthermore, it emerged that positive gestures activate more the left DLPFC, with an increase in inter-brain connectivity in DLPFC and SFG. The present study revealed the relevant function of the type and valence of gestures in affecting intra- and inter-brain connectivity.